A transition-metal-free fast track to flavones and 3-arylcoumarins. Issue 77 (14th September 2017) - Golshani, Mostafa; Khoobi, Mehdi; Jalalimanesh, Nafiseh; Jafarpour, Farnaz; Ariafard, Alireza
Abstract : A first general transition-metal free line for the construction of versatile chromenone based drug candidates is devised. Abstract : A highly regioselective and transition-metal free one-pot arylation of chromenones with arylboronic acids has been achieved employing K2 S2 O8 . The procedure consists of a sequence of some reactions including an arylation/decarboxylation cascade and proceeds well in aqueous media to afford biologically interesting flavones and 3-arylcoumarins. This method exhibited excellent selectivity and functional group tolerance under mild conditions. The reaction also showed perfect efficacy for the preparation of styryl coumarins.